Case report: Therapeutic response for new daily persistent headache by a tumor necrosis factor alpha antagonist, lithium. (27th March 2021) - Bancalari, Ernesto M; Wicht, Astrid
New daily persistent headache (NDPH) is an uncommon, treatment-resistant primary headache disorder that was first describe by Vanast in 1986 as a benign syndrome. Elevated TNF-alpha levels on CSF of NDPH patients as a possible cause of this disease. TNF-alpha inhibitors like doxycycline, venlafaxine and montelukast have been used in the past with relative good success. Lithium, used in Cluster Headache, has anti-inflammatory effects by inhibition of glycogen synthase kinase-3 (GSK3). This mechanism of action reduces production of inflammatory IL-6, IL-1 beta and TNF-alpha production by microglia, astrocytes and other immune cells. We report a NDPH patient that responded successfully to the administration of lithium after trying multiple treatments. We propose lithium, a TNF-alpha Inhibitor, as an effective treatment for refractory cases of NDPH.